Electric Power Optimizing Of Solar Panel SystemThrough Solar Tracking Implementation; A Case Study in Pekanbaru - Prayitno, Adhy; Irvan, Muhammad; Nurharsanto, Sigit; Yantoa, Wahyu Fajar (International Series on Interdisciplinary Science and Technology, 2017)
Observations and measurements have been conducted towards a solar panel electric power output that is utilized by a solar tracking system. The electrical power output depends on the position of the sun and time and the direction of the panel surface against the angle of the incident light. For power optimization, the solar panel surface should always be directed perpendicular to the direction of the sunlight falling to the surface of the panel. The application of the solar tracking system controlled by a micro controller gives the expected results. The electrical power output of a static solar panel mounted on a fixed position becomes the benchmark of the output electric power value in this study. The measurement results of the electric power output of the solar panel with sun tracking system shows a significant increase in sunny weather conditions.The average increase of that is about 57.3%.Keywords: LDR, micro controller, optimal power output, performance improvment, sun tracking,